Hubungan antara Keberfungsian Keluarga dan Fear of Missing Out (FoMO) dengan Kecanduan Internet pada Remaja - Ruby, Arcivid Chorynia; Prihartanti, Nanik; Partini, Partini (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
Internet addiction can be influenced by family functioning because there are no family members to interact with after school, as well as Fear of Missing Out (FoMO) related to the purpose and timing of internet use because it is easier to get information via the internet compared to asking the teacher or family, as well as a sense of  anxious if you do not know the latest information about something that is happening.  This study aims to determine the correlation between family functioning and Fear of Missing Out (FoMO) with internet addiction in adolescents.  The research subjects were 238 students of junior high school in Sukoharjo using linear regression data analysis techniques.  The results showed that 1) There is a very significant correlation between family functioning and Fear of Missing Out (FoMO) with internet addiction in adolescents; 2) There is a very significant correlation between family functioning and internet addiction, where the higher the family functioning, the internet addiction getting lower; 3) There is a very significant correlation between Fear of Missing Out (FoMO) and internet addiction in adolescents, where the higher the Fear of Missing Out (FoMO), the higher internet addiction will also be higher. Kecanduan internet dapat dipengaruhi oleh faktor keberfungsian keluarga karena tidak adanya anggota keluarga yang bisa diajak berinteraksi sepulang sekolah, serta Fear of Missing Out (FoMO) yang berkaitan dengan tujuan dan waktu penggunaan internet karena mudahnya mendapatkan informasi melalui internet dibandingkan bertanya pada guru atau keluarga, serta rasa cemas apabila tidak mengetahui informasi terbaru mengenai sesuatu yang sedang terjadi. Penelitian ini bertujuan untuk mengetahui hubungan antara keberfungsian keluarga dan Fear of Missing Out (FoMO) dengan kecanduan internet pada remaja. Subjek penelitian berjumlah 238 siswa SMP Negeri di Sukoharjo dengan menggunakan teknik analisis data regresi linier. Hasil penelitian menunjukkan bahwa 1) Terdapat hubungan yang sangat signifikan antara keberfungsian keluarga dan Fear of Missing Out (FoMO) dengan kecanduan internet pada remaja; 2) Terdapat hubungan yang sangat signifikan antara keberfungsian keluarga dengan kecanduan internet, dimana semakin tinggi keberfungsian keluarga, maka kecanduan internet semakin rendah; 3) Terdapat hubungan yang sangat signifikan antara Fear of Missing Out (FoMO) dengan kecanduan internet pada remaja, dimana semakin tinggi  Fear of Missing Out (FoMO), maka kecanduan internet juga akan semakin tinggi.